EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA TERHADAP PRESTASI BELAJAR IPAS PADA SISWA KELAS IV SD MUHAMMADIYAH NGLUWAR MAGELANG - Ratna Riantiarna; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article evaluates the effect of Canva-based interactive learning media on the science learning achievement of fourth-grade students at Muhammadiyah Ngluwar Elementary School, Magelang. The problem is based on suboptimal student achievement due to a lack of media innovation in the classroom. Using a quasi-experimental approach with a nonequivalent control group design, this study involved 56 respondents distributed into two classes. Data evaluation techniques were conducted through a series of statistical tests, including normality tests, homogeneity tests, independent sample t-tests, and N-Gain and effect size calculations. Empirical findings demonstrated an advantage for the experimental class, with an average score of 82.50 compared to the control class, with a score of 67.86. A significance level of 0.000 supported the hypothesis. Although competency growth through N-Gain was moderate, the effect size of 1.192 indicated a high influence of this media. Overall, the use of Canva as an interactive media has proven effective in improving students’ academic achievement in science.